Extending the Microtubule/Microfibril Paradigm : Cellulose Synthesis Is Required for Normal Cortical Microtubule Alignment in Elongating Cells - Fisher, Deborah D. (American Society of Plant Physiologists, 1998)
The cortical microtubule array provides spatial information to the cellulose-synthesizing machinery within the plasma membrane of elongating cells. Until now data indicated that information is transferred from organized cortical microtubules to the cellulose-synthesizing complex, which results in the deposition of ordered cellulosic walls. How cortical microtubules become aligned is unclear. The literature indicates that biophysical forces, transmitted by the organized cellulose component of the cell wall, provide a spatial cue to orient cortical microtubules. This hypothesis was tested on tobacco (Nicotiana tabacum L.) protoplasts and suspension-cultured cells treated with the cellulose synthesis inhibitor isoxaben. Isoxaben (0.25–2.5 μm) inhibited the synthesis of cellulose microfibrils (detected by staining with 1 μg mL(−1) fluorescent dye and polarized birefringence), the cells failed to elongate, and the cortical microtubules failed to become organized. The affects of isoxaben were reversible, and after its removal microtubules reorganized and cells elongated. Isoxaben did not depolymerize microtubules in vivo or inhibit the polymerization of tubulin in vitro. These data are consistent with the hypothesis that cellulose microfibrils, and hence cell elongation, are involved in providing spatial cues for cortical microtubule organization. These results compel us to extend the microtubule/microfibril paradigm to include the bidirectional flow of information.